Մաքրավանքի նորահայտ խաչքարերը (IX-XI դդ.) - Գրիգորյան, Ավետիս; Ասատրյան, Գեղամ (Մատենադարան)
The article presents the peculiarities of the IX-XI centuries khachʻkʻars excavated in 2018 in Makʻravankʻ. The newly discovered khachʻkʻars are conditionally divided into three groups: those with simple composition, elaborated ones and examples enriched with plant elements. The newly discovered khachʻkʻars are characterized not only by the common patterns of the khachʻkʻar art but also by some local features which became apparent since the XII century. The study of the newly discovered khachʻkʻars arouses some difficulties because of the lack of dated inscriptions and less prominent formal peculiarities. В статье представлены особенности хачкаров IX-XI веков, найденных в 2018 при раскопках в Макраванкском монастырском комплексе. Новонайденные хачкары условно разделены на три группы: с простой композицией, усложненной и обогащенной растительными элементами. Недавно обнаруженным хачкарам свойственны не только общие закономерности развития искусства хачкаров, но также некоторые местные черты, проявившиеся с XII века. Изучение новонайденных хачкаров сопряжено с некоторыми трудностями, из-за отсутствия датированных надписей и менее выраженных формальных особенностей.
Keywords: Հայ եկեղեցու պատմություն